Methods for assessing the regenerative responses of neural tissue - Poser, Steven W.; Rueger, Maria Adele; Androutsellis-Theotokis, Andreas (Springer, 2014)
In order to establish novel therapeutic paradigms and advance the field of regenerative medicine, methods for their effective implementation as well as rigorous assessment of outcomes are critical. This is especially evident and challenging in the context of treating complex and devastating neurodegenerative disorders, such as Parkinson’s disease, multiple sclerosis, and ischemic stroke. Stem cell-based approaches offer great promise in addressing these conditions. Here, we demonstrate an approach for identifying factors that mobilize endogenous neural stem cells in the repair and recovery of the central nervous system of rodents, involving site-specific administration of growth factors that activate particular signal transduction pathways, and that allows for the assessment of outcome utilizing magnetic resonance imaging and immunohistochemistry.